Evaluation and effects of STEAM-PBL on mathematics interest and numeracy skills on elementary school - Ranak, Lince; Rustam, Rustam; Ero, Priska Efriani Luansi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2023)
The STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach with a project-based learning model is one of the learning strategies that contribute to the development of 21st century skills. But how does this strategy apply to learning mathematics in elementary schools? In addition, can this strategy affect the interest in learning mathematics and numeracy skills of elementary school students? This study aims to answer these questions as well as develop and evaluate its application in mathematics learning in elementary schools. The research method used is Design-Based Research (DBR) which is conducted through active collaboration between researchers and classroom teachers. Data collection used questionnaires, tests, observations and interviews. Based on statistical analysis of learning interest data and numeracy skills, a significance value of 0.00 <0.05 was obtained so it can be concluded that learning mathematics using a project-based STEAM approach has a positive and significant effect on mathematics learning interest and numeracy literacy skills of elementary school students. Then its implementation based on observations and interviews can be effective and improve students' abilities. However, its application also has shortcomings so that it must be properly prepared.